DEVELOPMENT OF LEARNING MODULES WITH DATA PRESENTATION MATERIALS TO INCREASE STUDENTS' INTEREST IN LEARNING - Telaumbanua, Lukas (Universitas Nias Raya, 2023)
The aim of the research is to develop a data presentation module to increase students' interest in learning. This type of research is research and development (R&D), with the ADDIE model. Qualitative and quantitative data analysis techniques. Validation results of the material section 4.26 valid category. The validation of media experts is 4.50 valid categories and the validation of linguists is 4.87 categories which are very valid. Practical results in confined classes and fields. The results of practicality in the limited trial using a student response questionnaire and a questionnaire of initial and final student learning interest, the results of the practicality percentage obtained a maximum value of 2.72 in the very practical category, the practicality test using a final learning interest questionnaire with a value of 4.9 in the very practical category. The practicality result in the field trial was 4.72 in the very practical category. The results of the effectiveness of the test module obtained an average score of 75 in the complete category. Hopefully the results obtained above can make further researchers easier to understand so as to increase student learning interest